The Effect of Reflective Blankets on Reducing Inadvertent Perioperative Hypothermia in Abdominal Surgery Patients: A Randomized Controlled Trial - Yava, Ayla; Güzel, Ali; Koyuncu, Aynur; Yava, Ayla; Koyuncu, Aynur (W.B. Saunders, 2025)
Purpose This study aimed to evaluate the effect of a reflective blanket on reducing perioperative hypothermia and on thermal comfort and shivering levels in patients undergoing abdominal surgery. Design The research is in the design of a randomized controlled clinical trial. Methods This randomized controlled trial, conducted between February 2022 and January 2023 in a public hospital, included 105 American Society of Anesthesiologists I and II patients undergoing laparoscopic cholecystectomy or umbilical hernia surgery. Patients were randomized into three groups: active warming (n = 35), reflective blanket (n = 35), and routine care (n = 35). The active warming and reflective blanket groups received 15 minutes of prewarming. Body temperature, shivering, and thermal comfort were assessed. Data were analyzed with SPSS 21.0 (IBM Corp) ( P < .05). Findings There were no statistically significant differences between the groups in terms of demographic and clinical characteristics ( P > .05). At the end of anesthesia, hypothermia was observed in 71.4% of patients in the control group, 42.9% in the intervention group and 28.6% in the reference group ( P < .05). Before clinical transfer, hypothermia persisted only in the control group (37.1%) and was not observed in the other two groups ( P < .001). Shivering was seen only in the control and intervention groups, while it was absent in the reference group ( P < .05). Thermal comfort scores were similar at baseline, but during the perioperative period, the reference group had the highest and the control group the lowest scores ( P < .01). Conclusions The use of reflective blankets was as effective as active warming in reducing the incidence of inadvertent perioperative hypothermia and shivering and increasing the level of thermal comfort perception in patients and provided superiority over the control group. © 2025 The American Society of PeriAnesthesia Nurses.
Keywords: Inadvertent perioperative hypothermia; Passive warming; Reflective blanket; Thermal comfort